(3JMaI GdCTQGa HeYQaI GdCWQGas - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s ((3YeQ Hf CMeO GdLQgei GdMfai s)
(3ChdgG (B:s
(3ef YWGA Hf GdSGFH GdKbaj Yf SYjO Hf MHjQ Yf GHf YHGS s
(3BNQgG (B:s
(3Edi (B: (3eMeO GHf YLdGf GdeOfi Yf YeQh Hf TYjH Yf CHjg Yf YHOGddg Hf YeQh Hf GdYGU s
(3GdfSNI HgG MhGTs
(3hgh ef Chd GdLRA (B22 (3Edi BNQ GdLRA (B31 (3ef JLRFI GdCUds
(3ocJH bHd SfI (B726(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs